2021
DOI: 10.1371/journal.pone.0258137
|View full text |Cite
|
Sign up to set email alerts
|

Online college English education in Wuhan against the COVID-19 pandemic: Student and teacher readiness, challenges and implications

Abstract: Online education, including college English education, has been developing rapidly in the recent decade in China. Such aspects as e-readiness, benefits and challenges of online education were well-researched under normal situations, but fully online language teaching on a large-scale in emergencies may tell a different story. A survey of 2310 non-English-major college students and 149 English teachers from three types of twelve higher education institutions in Wuhan was conducted to evaluate their readiness fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 53 publications
3
48
0
Order By: Relevance
“…In fact, they believed that presentation format, length and type of interaction had a great impact on online attention and enjoyment, or in other words, the longer and less interactive the presentation, the higher the risk of student distraction and disengagement in live online lessons. This was consistent with previous literature [15,16] stating that longer conversational turns may hinder interaction in SCMC, resulting in student disengagement. However, the novelty was that participants stressed the importance not only of length but also of format (games, collaborative dashboards) and type (peer-to-peer) of the presentations as key factors to enhance online student participation.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, they believed that presentation format, length and type of interaction had a great impact on online attention and enjoyment, or in other words, the longer and less interactive the presentation, the higher the risk of student distraction and disengagement in live online lessons. This was consistent with previous literature [15,16] stating that longer conversational turns may hinder interaction in SCMC, resulting in student disengagement. However, the novelty was that participants stressed the importance not only of length but also of format (games, collaborative dashboards) and type (peer-to-peer) of the presentations as key factors to enhance online student participation.…”
Section: Resultssupporting
confidence: 93%
“…Technologically, different studies have delved into the scarcity of digital resources in some educational contexts, poor connectivity resulting in delayed communication, lack of privacy and partly ineffective communication owing to the lack of nonverbal cues and true human contact [13]. Pedagogically, some constraints reported were low computer literacy, lack of teacher readiness as regards class management in live online platforms and low student interest and interaction partly due to longer conversational turns, which might result in student disengagement [14][15][16].…”
Section: Introduction 1synchronous Computer-mediated Communication (Scmc) In Language Learningmentioning
confidence: 99%
“…Many researchers have attempted to assess readiness factors that influence online learning performance by either confirming an existing model or expanding it with additional components (Dorsah, 2021;Zou et al, 2021). For example, Hung (2016) identified four teachers-as-learners' factors, including communication selfefficacy, institutional support, self-directed learning, and learning-transfer selfefficacy.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…For example, Hung (2016) identified four teachers-as-learners' factors, including communication selfefficacy, institutional support, self-directed learning, and learning-transfer selfefficacy. Zou et al (2021) considered other factors such as technology access and computer self-efficacy. Sailer et al (2021) suggested that the facilitating conditions provided by higher education institutions influence the context of teaching and learning significantly.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…The use of digital games in language learning has been the object of study in several publications over the last two decades [1][2][3][4][5]. Some works focused on the consequences of integrating such games in education and language learning, particularly as regards student motivation [6,7] and enjoyment [8,9], while others analyzed their impact on the development of certain language skills and components such as listening and speaking [10,11], reading and writing [12], grammar [13], and vocabulary [14][15][16]. Conversely, few articles examined the knowledge and attitudes of preservice teachers toward the integration of digital games in an English as a Foreign Language (EFL) classroom [17][18][19].…”
Section: Introductionmentioning
confidence: 99%